PERANAN TEHNOLOGI STEAMER DAN KUALITAS PELAYANAN DALAM PENINGKATAN KEUNTUNGAN BAGI PENGUSAHA ROTI - Joko Samboro; Nilawati Fiernaningsih; R. Sugeng Basuki (Publisher UPT P2M Politeknik Negeri Malang, 2015)
In that situation however, small companies will still exist in conducting its business activities, it is because of the high flexibility. The purpose of this paper is to find the problems by small firms / bread and provide appropriate solutions in order to achieve improvement of the knowledge and capabilities in the field of business operations in particular areas of the management of marketing and production and at the same time creating employment opportunities in the governance of economic activities of the community in the form of an increase in people's income . The methods used are: observation, then interviews, and simulations, to find the most suitable alternative in order to more effectively market their goods. The existence steamer machine, it can shorten the process that eliminate the possibility of a wry sense of bread.Display case with a combination of stanlees and glass, it can accommodate more goods and can be styled to be attractive. Printed plastic wrapper make product, more attractive and can be unique from brands. With the uniform and the additional knowledge of marketing management, especially quality of service, employers can attract buyers better.